2014
DOI: 10.7717/peerj.513
|View full text |Cite
|
Sign up to set email alerts
|

Hand infections: a retrospective analysis

Abstract: Purpose. Hand infections are common, usually resulting from an untreated injury. In this retrospective study, we report on hand infection cases needing surgical drainage in order to assess patient demographics, causation of infection, clinical course, and clinical management.Methods. Medical records of patients presenting with hand infections, excluding post-surgical infections, treated with incision and debridement over a one-year period were reviewed. Patient demographics; past medical history; infection sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…We report 114 cases of hand infections over a 1‐year period. Previous research has indicated low incidences of hand infections, with some hospitals reporting fewer than 20 infections per year; however, other studies have shown rates similar to ours . It appears hand infection incidence is highly dependent on the population residing in a hospital's catchment area.…”
Section: Discussionmentioning
confidence: 99%
“…We report 114 cases of hand infections over a 1‐year period. Previous research has indicated low incidences of hand infections, with some hospitals reporting fewer than 20 infections per year; however, other studies have shown rates similar to ours . It appears hand infection incidence is highly dependent on the population residing in a hospital's catchment area.…”
Section: Discussionmentioning
confidence: 99%
“…2 Acute infections of the hand are considered to be a significant cause of morbidity and mortality; when left untreated, they can lead to tissue destruction and loss of function or even permanent disability. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…1 Treatment requires a multifaceted approach combining proper antimicrobial therapy, immobilization, oedema control, and adequate surgical therapy. 1,3 Because of the potential for serious morbidity and complications, a combination of aggressive operative and medical therapy should be applied following an early identification in a timely fashion. 1,5 If any further information about the aetiology of the infection is needed, consultation from an infectious diseases specialist is useful in deciding on the appropriate antimicrobial regimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with data reported by other centers, S. aureus was the most commonly identified pathogen in culture overall. [18][19][20][21][22][23] The etiologic agents of hand infection were comparable between the DM and no-DM groups: rates of identification of all S. aureus, MRSA, gram-negative organisms, and polymicrobial cultures did not differ significantly between DM and no-DM groups. The literature describes the rates of culture of gram-negative organisms from hand infections as ranging from 51.1 to 73% in diabetics and 8 to 11.3% overall.…”
Section: Discussionmentioning
confidence: 99%